EL UNIVERSO PLÁSTICO Y SENSORIAL DE LA MANO (WONG KAR WAI, 2004) - Ana MELENDO (Fonseca, Journal of Communication, 2023)
In this article, we show how Wong Kar Wai, heir to a filmography closely linked to cinematographic modernity, explores themes such as loneliness, melancholy, or self-absorption in his short film The Hand (2004). These themes, together with his study of geometry, saturated colours and pictorial qualities through the prism of metaphysical realism, give rise to purely optical, sonorous and tactile situations. In this way, the Chinese film director reveals, through the presence of a body fragment and metonymy, the colourful and sonorous textures that form the sensory-motor spaces of the underworld in which the story is set